Locational Tendency of Mosques in Bursa, Turkey: Regional Study Using Geographic Information System - Kensuke, Kit; Yasushi, Asami; DOSTOĞLU, NESLİHAN (Locke Science Publishing Company, Inc., 2004)
Locational tendency of mosques in Bursa, Turkey ; is analyzed in this paper using three-dimensional operations of the Geographic Information System (G.I.S.). After constructing Triangulated Irregular Network (T.I.N.) in Bursa, the relationships with slope and road networks, as well as the visibility area of mosques, are analyzed. The results show that large mosques have been built on flat land on hills so that their visibility in the city is as high as possible. This suggests that the Ottoman sultans controlled the development of the city by the strategic location of mosques. In short, this paper uses new technology as a tool in investigating the motives behind the design and construction of Bursa in the past and implies that similar methods can be utilized for spatial analysis of urban development in general.